Waste-derived thermal storage solutions for sustainable solar desalination using discarded engine oil and paraffin wax: A techno-environmental feasibility evaluation - Suraparaju, Subbarama Kousik; Mahendran, Samykano; Natarajan, Sendhil Kumar; Rajamony, Reji Kumar; Pandey, Adarsh Kumar (Elsevier, 2024)
The valorization and repurposing of waste materials for sustainable outcomes and environmental mitigation are gaining prominence. This investigation explores the feasibility of repurposing discarded automotive engine oil as a viable means of energy storage in solar thermal desalination applications. A novel approach combining discarded engine oil with Paraffin wax in equal parts by volume is proposed as a composite energy storage (CES) to enhance nocturnal production and efficiency. The experimental findings show that the composite energy storage system has 26.54 % higher thermal conductivity and 44.66 % greater specific heat energy storage capacity compared to pure paraffin wax. Comparing the Desalination System with Engine Oil-based Energy Storage (DSEES) to a Traditional Solar Desalination System (TSDS) without energy storage, considering water and absorber temperatures and distillate production, reveals compelling advantages. DSEES exhibits remarkable temperature increases of 14 % in the basin and 11 % in water, alongside a significant 52.72 % rise in distillate production rates, yielding 3.36 and 3.16 l/sq.mt compared to TSDS's 2.2 and 2.1 l/sq.mt over two testing days. Cost analysis indicates DSEES's 33.7 % lower cost per liter and 33.8 % shorter payback period relative to TSDS. Furthermore, environmental assessment highlights DSEES's 60.8 % greater net carbon credit, indicating reduced ecological impact.